The Maslahah of State Policy in Responding to Unregistered Marriage: Inclusion of Unregistered Marriage on The Family Card - Billah, Mu'tashim (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
Based on Minister of Home Affairs regulations No. 108 and No. 109 of 2019, unregistered (siri) marriage couples can now record their marriage in the Family Card. This article aims to analyze the policy of issuing Family Cards for unregistered marriage couples using the Islamic jurisprudence (ushul fiqh) approach. This article is a literature study, with data sourced from the Minister of Home Affairs regulations and various related literatures. The obtained data is then analyzed using a normative-philosophical approach, specifically ushul fiqh theories such as the concepts of public interest (maslahah) and preventing harm (adz-dzari’ah). The article argues that in every policy, there will be potential benefits (maslahah) and harms (mudharat). In the policy of recording unregistered marriages, the government needs to close the means that cause harm (saddu al-dhariah) to ensure this policy is not interpreted as a form of legalizing unregistered marriages. The government also needs to open the means that lead to benefits (fathu al-dhariah) so that the goal of fulfilling children's civil rights with the basis of having a birth certificate, and the purpose of the Marriage Law, namely the validity of marriage, can be achieved through the use of unregistered marriage data for expediting the marriage legalization process (itsbat nikah) in Religious Courts. The conclusion of this article is that to achieve the ideal policy objectives, aspects of benefits and harms need to be considered. This article contributes to understanding state policies from the perspective of ushul fiqh and indicates that it remains a relevant approach.